On the Coherence of Plato's Philosophers. Issue 2 (19th April 2018) - Davis, Michael
Abstract: Because Plato's Philosophers : The Coherence of the Dialogues is such a monumental book, understanding its own coherence is a daunting task. The dialogue Theaetetus has as its theme the problem of knowledge, and so the part of Plato's Philosophers that deals with the Theaetetus seems a promising place to begin to think through what Zuckert's book means to be as a whole. In the Theaetetus we learn how knowledge, as a story that must begin and unfold for us in time, while necessarily partial, provides indirect, if imperfect, access to the whole and leads to a kind of self- knowledge. Plato makes this self-knowledge, the true goal of philosophy, most fully manifest in the drama of the life of his philosopher, Socrates, to which Plato's Philosophers, in meticulously tracing the dramatic order of the dialogues, means to provide access.